Physical Characteristics of Foot-Hill Soils of Punjab in Relation to Water Erosion - Singh, N.T.; Verma, K.S. (Journal of Soil and Water Conservation, 2022)
The tract along the foot hills of Punjab is comprised of rolling and moderately to strongly sloping soil areas. Annual rainfall ranges from 75 100cm. Agriculture on most of these soils depends upon rainfall, a large part of which is received during the monsoon months. Because of the excessive relief and poor management of these soils, most of the rainwater runs off the fields into small seasonal streams called thos’. The run-off water and the high velocity water have severely eroded these soils. Moreover very little water enters these soils during short duration storms, most of it thus remaining unavailable for plant growth. Absene of adequate plant cover and low intake rates of these soils have greatly curtailed the success of contour bunding programme in this area.